Angry Management Three Novellas - Crutcher, Chris (New York : Greenwillow Books, 2009)
A collection of three stories featuring characters from earlier books by Chris Crutcher.
Nak -- Montana wild -- Meet me at the gates, Marcus James.
Keywords: Short stories; Short stories, American